anonymous
  • anonymous
HELP PRECALC MEDALS 1.) Find an equation for the nth term of the arithmetic sequence. a14 = -33, a15 = 9 an = -579 + 42(n + 1) an = -579 + 42(n - 1) an = -579 - 42(n + 1) an = -579 - 42(n - 1) 2. Find an equation for the nth term of the arithmetic sequence. -15, -6, 3, 12, ... an = -15 + 9(n + 1) an = -15 x 9(n - 1) an = -15 + 9(n + 2) an = -15 + 9(n - 1) 3. Find an equation for the nth term of the sequence. -3, -12, -48, -192, an = 4 • -3n + 1 an = -3 • 4n - 1 an = -3 • 4n an = 4 • -3n
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
misssunshinexxoxo
  • misssunshinexxoxo
Kindly separate these questions or tell us what you believe the answer is
SolomonZelman
  • SolomonZelman
(Note: given two point. That can be an exponential function - geometric sequence, or a linear function - arithmetic sequence. However, I conclude from the answer choices that this #1 is arithm. sequence.)
SolomonZelman
  • SolomonZelman
\(\large\color{black}{ \displaystyle a_{14}=-33 }\), \(\large\color{black}{ \displaystyle a_{15}=9 }\) since we are talking about a geometric sequence \(\large\color{black}{ \displaystyle {\rm d}=a_{15}-a_{14}=9-(-33)=? }\)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

SolomonZelman
  • SolomonZelman
because in geometric sequence, d, the common difference between the terms is `(a term) - (a term before it)` so, \(\large\color{black}{ \displaystyle {\rm d}=a_{n-1}-a_{n}={\small(\rm in~this~case)}~~a_{15}-a_{14}=9-(-33)=? }\)
anonymous
  • anonymous
@SolomonZelman an = -579 + 42(n - 1) (?)
anonymous
  • anonymous
@SolomonZelman

Looking for something else?

Not the answer you are looking for? Search for more explanations.